Lessons learnt from pilot field test of a comprehensive advocacy program to support health promoting schools’ project in Iran - Towhid Babazadeh (Health Promotion Perspectives, 2017)
Background: Health promoting schools (HPS) project is currently being used in Iran but many challenges still lie ahead. The present study aimed, to test feasibility of implementing a comprehensive advocacy program (CAP) to overcome the obstacles and problems associated with the consummation of school health programs based on the HPS framework.